2014
DOI: 10.5694/mja13.10710
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of variation in colorectal cancer care and outcomes in New South Wales: a population‐based health data linkage study

Abstract: Patient characteristics should be included in risk-adjustment models for comparing outcomes between hospitals and for quantifying hospital variation. Further exploration of the reasons why certain hospitals and patients appear to be at risk of poorer care is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 20 publications
3
35
1
Order By: Relevance
“…Advanced stage, older age, emergency admission and comorbidity increased the risk of postoperative deaths following resection for CRC. Thirty‐day postoperative mortality was also higher among non‐metropolitan than metropolitan residents, which contrasts with the findings of Jorgensen et al (Australia) and Helewa et al (Canada) who found no regional disparities in 30‐day mortality, after case‐mix adjustment. International studies suggest higher volume hospitals are better placed to manage complications during surgery .…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Advanced stage, older age, emergency admission and comorbidity increased the risk of postoperative deaths following resection for CRC. Thirty‐day postoperative mortality was also higher among non‐metropolitan than metropolitan residents, which contrasts with the findings of Jorgensen et al (Australia) and Helewa et al (Canada) who found no regional disparities in 30‐day mortality, after case‐mix adjustment. International studies suggest higher volume hospitals are better placed to manage complications during surgery .…”
Section: Discussioncontrasting
confidence: 93%
“…Emergency admission was consistently associated with poorer outcomes for other short‐term outcomes which is consistent with other studies . Obstruction, bleeding and perforation are the main causes of emergency admission , making surgical intervention more urgent and more complex.…”
Section: Discussionsupporting
confidence: 88%
“…Linked NSW hospital and death data are commonly used to monitor surgical resection rates and associated mortality rates. [36][37][38] The validity of these data needs to be checked when service agencies use them to monitor service performance. This validation process is illustrated with pancreatic cancer data.…”
Section: Increasing Timeliness Of Service Monitoringmentioning
confidence: 99%
“…41 Registry data linkage with administrative data enables assessment of patterns of care and other performance indicators for health-system monitoring. [36][37][38][39][40] Administrative data may lack the quality of customised registry data, but they complement the registry data and are adequate for showing broad populationwide patterns of care. 34,[36][37][38] Clinical registries may be used to validate linked administrative data in instances where these data cover common patient groups.…”
Section: Emerging Rolesmentioning
confidence: 99%
See 1 more Smart Citation